2020
DOI: 10.1038/s41598-020-63592-6
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm shift in aerosol chemical composition over regions downwind of China

Abstract: A rapid decrease in pM 2.5 concentrations in china has been observed in response to the enactment of strong emission control policies. From 2012 to 2017, total emissions of SO 2 and no x from china decreased by approximately 63% and 24%, respectively. Simultaneously, decreases in the PM 2.5 concentration in Japan have been observed since 2014, and the proportion of stations that satisfy the pM 2.5 environmental standard (daily, 35 µg/m 3 ; annual average, 15 µg/m 3 ) increased from 37.8% in fiscal year (FY) 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…The ratio of PM 2.5 concentration in 2019 to that in 2011 is 0.43 in Beijing, 0.69 in Shanghai, and 0.54 in Guangzhou, indicating that the PM 2.5 concentrations have decreased significantly, which is likely due to an effect of the emission control measures in China. This indicates that the impact of transboundary PM 2.5 on Japan is also decreasing, as pointed out by Uno et al (2020) [14]. PM 2.5 concentrations have also shown a decreasing trend since 2015, at the three sites in South Korea.…”
Section: General Characteristics Of Air Quality In Japansupporting
confidence: 65%
“…The ratio of PM 2.5 concentration in 2019 to that in 2011 is 0.43 in Beijing, 0.69 in Shanghai, and 0.54 in Guangzhou, indicating that the PM 2.5 concentrations have decreased significantly, which is likely due to an effect of the emission control measures in China. This indicates that the impact of transboundary PM 2.5 on Japan is also decreasing, as pointed out by Uno et al (2020) [14]. PM 2.5 concentrations have also shown a decreasing trend since 2015, at the three sites in South Korea.…”
Section: General Characteristics Of Air Quality In Japansupporting
confidence: 65%
“…The PM 2.5 concentrations in Fukuoka have been reported to be influenced by cross-border pollution from China. 29) As the concentration of PM 2.5 in China decreased, the concentration in Fukuoka was found to decrease from 2013 to 2016 29) and from 2014 to 2019. 30) Therefore, one of the causes of the high cytotoxicity levels in FY2016 may have been due to the effect of cross-border pollution from China.…”
Section: Fig 2 Concentrations Of Ammonium and Sulfate Ions (Mg/l) Of Coarse And Fine Particulatesmentioning
confidence: 97%
“…Over 2013-2017, anthropogenic emissions of nitrate precursors of NO x and NH 3 were reduced by 20.7 and 3.4% in China, respectively, and the concentrations of nitrate were reduced in China. However, the changes in anthropogenic emissions over China led to an increasing trend of nitrate in South Korea and Japan, which can be explained by that the reductions in SO 2 emissions changed the balance of the ammonia-nitric acid-sulfuric acid-water system, creating free NH 3 that reacted with HNO 3 to form NH 4 NO 3 (Bae et al, 2021;Uno et al, 2020).…”
Section: Frontiers In Environmentalmentioning
confidence: 99%
“…Kanaya et al (2020) analyzed the changes in black carbon (BC) and PM 2.5 over 2009-2019 at Fukue island in Japan, and reported that concentrations of BC and PM 2.5 decreased by 48 and 21%, respectively. Uno et al (2020) reported that the observed surfacelayer PM 2.5 in Japan decreased in recent years, and the proportion of stations that satisfied the PM 2.5 air quality standard increased from 37.8% in 2014 to 89.9% in 2017. Bae et al (2021) showed that, from 2015 to 2018, the observed PM 2.5 concentrations averaged over 344 monitoring stations across South Korea decreased by 4.3% per year and the MODIS AOD in South Korea decreased by 4.7% per year.…”
Section: Introductionmentioning
confidence: 99%